2018
DOI: 10.1152/ajpheart.00277.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 as a regulator of valve myofibroblast mechanobiology

Abstract: Cadherin-11 (CDH11) is upregulated in a variety of fibrotic diseases, including arthritis and calcific aortic valve disease. Our recent work has identified CDH11 as a potential therapeutic target and shown that treatment with a CDH11 functional blocking antibody can prevent hallmarks of calcific aortic valve disease in mice. The present study investigated the role of CDH11 in regulating the mechanobiological behavior of valvular interstitial cells believed to cause calcification. Aortic valve interstitial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…However, permanent loss of CDH11 in this mouse model may cause compensatory changes that increase the severity of cardiac damage after MI. Cdh11 -/-valve interstitial cells have reduced contractility, 16 which we also observed in Cdh11 -/-CFs, but notably did not observe in wild type CFs treated acutely with SYN0012 (cf. Figure S11).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, permanent loss of CDH11 in this mouse model may cause compensatory changes that increase the severity of cardiac damage after MI. Cdh11 -/-valve interstitial cells have reduced contractility, 16 which we also observed in Cdh11 -/-CFs, but notably did not observe in wild type CFs treated acutely with SYN0012 (cf. Figure S11).…”
Section: Discussionsupporting
confidence: 69%
“…Note that increased CDH11 expression is known to be a hallmark of myofibroblast phenotype in other cardiovascular cell types, such as aortic valve interstitial cells. 16 At both three and seven days post-MI, the majority of CDH11 + BMDCs were myeloid lineage macrophages with either M1-like or M2-like polarization, with the highest expression in M2-like macrophages ( Figure 1D-F). The time-dependent expression of CDH11 in the ischemic heart suggests that targeting of CDH11 after MI has the potential to affect both early tissue breakdown and inflammation -driven by macrophages -as well as later collagen deposition and remodeling -driven by myofibroblasts -to result in significant functional improvement after infarct.…”
Section: Discussionmentioning
confidence: 94%
“…Increased expression of CDH11 is observed in vitro upon TGFβ1‐stimulated activation of lung fibroblasts into myofibroblasts and in vivo during lung fibrosis . Consequently, increased CDH11 expression is both an indicator of myofibroblastic activation and thought to be a part of the positive feedback loop that fuels activation and persistence of myofibroblasts in fibrosis . Given our observation of trends in increased TGFβ1 expression with statistical increases in YAP nuclear localization and CDH11 expression in 2.5D culture on both soft and stiff matrices relative to 2D culture, we speculate that having matrix on all sides surrounding highly‐activated cells (i.e., spread, clustered, αSMA positive cells in 2.5D culture) may provide a positive feedback loop that further promotes cell activation.…”
Section: Resultsmentioning
confidence: 66%
“…Cadherin-11 (CDH11) is an adhesion protein mainly expressed in mesenchymal tissues that regulates the differentiation and function of osteoblasts. CDH11 was identified to participate in multiple BPs including bone formation, cellular signal transduction, tumor invasion, and metastasis (Lee et al, 2007;Li et al, 2012;Langhe et al, 2016;Madarampalli et al, 2019;Yuan et al, 2019a), and also play important roles in developmental and pathogenic mechanisms of heart valve (Zhou et al, 2013;Bowler et al, 2018). A recent study found that CDH11 contributed to inflammation-driven fibrotic remodeling after myocardial infarction (Schroer et al, 2019), which indicated that the increased CDH11 might be involved in the development of HF through inflammatory response.…”
Section: Discussionmentioning
confidence: 99%